Berberine Improves Chemo-Sensitivity to Cisplatin by Enhancing Cell Apoptosis and Repressing PI3K/AKT/mTOR Signaling Pathway in Gastric Cancer - Kou, Yingying; Tong, Bending; Wu, Weiqing; Liao, Xiangqing; Zhao, Min (Frontiers in Pharmacology, 2020)
Berberine improves chemo-sensitivity to cisplatin by enhancing cell apoptosis and repressing PI3K/AKT/mTOR signaling pathway in gastric cancer